Interpretasi HAM dalam Ideologi Pancasila dan Implikasinya terhadap Persatuan dan Kesatuan di Indonesia - Ario Putra (Badan Strategi Kebijakan Hukum, 2022)
Human values in the form of human rights are also included in the Pancasila ideology. This research was conducted to contribute to academic development related to human rights issues in Indonesia. The method used in this research is descriptive exploratory. This research is library research. The data collection method is through classifying and analyzing data. The data analysis method in this study is through interpretation and analysis methods. Human rights in Indonesia experience various forms of dynamics that are full of struggle in their enforcement. Ancestors in the past or leaders in the present have made multiple attempts to uphold human rights in Indonesia. Human rights in Indonesia originate from the Pancasila ideology. Therefore, human rights in Indonesia receive strong guarantees because they are based on the Pancasila ideology. Unity in Indonesia will be achieved if all Indonesians can apply human rights values in their lives.